Unveiling Morphological Variability in Rice (Oryza sativa L.) Restorer Lines for Trait Optimization through DUS Characterization and Diversity Analysis - Patel, Teena; Singh, S. K.; Paliwal, Shruti; Anand, Kumar Jai (International Journal of Economic Plants, 2025)
The experiment was conducted during the kharif season (July to November, 2020) at the Seed Breeding Farm, Rice Improvement Project, Department of Plant Breeding & Genetics, College of Agriculture, Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur, Madhya Pradesh, India to investigate the morphological variability in rice (Oryza sativa L.) restorer lines. A total of eighty restorer lines were evaluated and morphologically characterized in accordance with the Distinctness, Uniformity, and Stability (DUS) guidelines. Additionally, the Shannon-Weaver diversity index was calculated for all the observed traits, providing insights into the genetic diversity present within the lines studied. The results indicated significant variability and diversity in traits such as color of stigma, sterile lemma color, density of pubescence of lemma, distribution of awns, and attitude of flag leaf blade (both early and late stages). This variation will be instrumental in selecting specific genotypes for protection, conservation, and further breeding programs. Conversely, minimal variability was observed in traits such as color of tip of lemma, anthocyanin coloration of the keel, panicle exertion, anthocyanin coloration of internodes, anthocyanin coloration of the apex, and leaf auricles. Traits consistently present across all the genotypes such as leaf collar, leaf ligule, split shape of ligule, white ligule color, drooping curvature of the panicle main axis, presence of secondary branching of panicle, and semi-erect panicle branches were determined to be monomorphic, indicating uniformity among all genotypes for these characteristics.